Faktor-Faktor yang Berhubungan dengan Perilaku Pengelolaan Sampah Rumah Tangga Di Kelurahan Cilandak Barat Kecamatan Cilandak Tahun 2022 - Rizky Andriyanto; Fini Fajrini; Nur Romdhona; Noor Latifah (Jurnal Ilmiah Wahana Pendidikan, 2023)
MENLHK, 2021 Recorded that South Jakarta is the city with the highest waste generation with a total waste generation of 1,937.54 tons/day or the equivalent of 707,201.35 tons/year. In Cilandak District itself in 2022 the volume of organic waste processed from Cilandak District is between 300 and 700 kilograms per day (Folmer, 2022). This study aims to find out "Factors Associated with Household Waste Management Behavior in West Cilandak Village, Cilandak District in 2022." The research was conducted in January 2023 in West Cilandak Village. This study used a cross sectional study design. The population in this study was 150 housewives in Cilandak Barat Village. The sample for this study was 150 people who were selected using stratified random sampling. The data in this study used instruments, then analyzed using testsWho Square with α=0.05. The results showed that 42% of the 150 respondents who behaved badly, and there was a relationship with the education variable (p value = 0.004) knowledge (p value 0.003), attitude (p value = 0.001), and infrastructure (p value = 0.000) with household waste management behavior. There is no age relationship (p value = 0.725) with household waste management behavior. Factors related to household waste management behavior include education, knowledge, attitudes, and infrastructure. Meanwhile, age is not related to household waste management behavior. It is necessary to participate in good activities if the government organizes these activities in order to increase knowledge on waste management, especially for housewives who still have insufficient knowledge.